NO MERCY, NO LENIENCY : COMMUNIST MISTREATMENT OF BRITISH PRISONERS OF WAR IN KOREA - Cunningham, Cyril; Foot, M.R.D. (Barnsley, Yorkshire : Pen & Sword MILITARY, an imprint of Pen & Sword Books Ltd., 2020)
This is the most authoritative and comprehensive British account ever published of the brutal North Korean and Chinese mistreatment of British POWs during the Korean War. The author, a psychologist, was a Scientific Advisor to the POW Intelligence Organisation during the Korean War. He explains in detail how many prisoners were bribed, starved, flogged and tortured into informing on their compatriots and infiltrated into every prisoner group to sniff out potential progressives and reactionaries.
Includes index
Keywords: Korean War, -- 1950-1953 -- Prisoners and prisons; Prisoners of war -- Great Britain; Prisoners of war -- Korea (North)